(untitled) (Ingeniería, Sostenibilidad y Sociedad, 2021)
Our project is based on the creation of cannabis-based tampons, as the oil from this plant has the power to act favorably on the uterine muscles, serving as a pain reliever for menstrual cramps. The idea originated in California, and we decided to adapt it mainly in the Norte de Santander region, as this product is not available in this area. Menstrual cramps have been a problem throughout history, as at least 75% of women suffer from menstrual pain, some more severe than others, and often pills fail to relieve this uncomfortable pain. The tampon was invented in the early 20th century, and at that time, this product was taboo. Over the years, tampons had to overcome many social stigmas in order to establish themselves in the market, with the result that many women today prefer to use tampons rather than sanitary pads. Our initiative stems from a desire to provide a solution to a problem that has affected many women over time. We want to offer comfort, hygiene, and smiles.